2018
DOI: 10.1186/s13068-018-1176-y
|View full text |Cite
|
Sign up to set email alerts
|

A pyruvate carbon flux tugging strategy for increasing 2,3-butanediol production and reducing ethanol subgeneration in the yeast Saccharomyces cerevisiae

Abstract: BackgroundThe yeast Saccharomyces cerevisiae is a promising host cell for producing a wide range of chemicals. However, attempts to metabolically engineer Crabtree-positive S. cerevisiae invariably face a common issue: how to reduce dominant ethanol production. Here, we propose a yeast metabolic engineering strategy for decreasing ethanol subgeneration involving tugging the carbon flux at an important hub branching point (e.g., pyruvate). Tugging flux at a central glycolytic overflow metabolism point arising f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 57 publications
(77 reference statements)
1
37
0
Order By: Relevance
“…The 23BD is biologically synthesized from two molecules of pyruvate by four-step reactions catalyzed by acetolactate synthase (ALS), acetolactate decarboxylase (ALDC), and butanediol dehydrogenase (BDH). In this study, a plasmid constructed in the previous study (pATP426-als Lp Op -aldc Ll Op -BDH1, als Lp Op , acdc Ll Op , BDH1 : codon-optimized ALS and ALDC genes derived from Lactobacillus plantarum and Lactococcus lactis and the BDH genes derived from S. cerevisiae [6]) was introduced in S. cerevisiae BY4742 (SCM043 strain) for cytosolic 23BD production.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 23BD is biologically synthesized from two molecules of pyruvate by four-step reactions catalyzed by acetolactate synthase (ALS), acetolactate decarboxylase (ALDC), and butanediol dehydrogenase (BDH). In this study, a plasmid constructed in the previous study (pATP426-als Lp Op -aldc Ll Op -BDH1, als Lp Op , acdc Ll Op , BDH1 : codon-optimized ALS and ALDC genes derived from Lactobacillus plantarum and Lactococcus lactis and the BDH genes derived from S. cerevisiae [6]) was introduced in S. cerevisiae BY4742 (SCM043 strain) for cytosolic 23BD production.…”
Section: Resultsmentioning
confidence: 99%
“…In S. cerevisiae cells, a large amount of pyruvate is consumed by the synthesis of cell components, ethanol production, and respiration in the mitochondrion. Several studies reported that the knockout or control of ethanol biosynthesis pathway genes in S. cerevisiae improves the production of the pyruvate-derived chemicals [3, 4, 6, 7]. In Escherichia coli , decreasing the citrate synthase expression by CRISPER/Cas9 system increased the n -butanol yield [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the concentration of 2,3-BDO (178 g/L) by the engineered polyploid S. cerevisiae strain (YG01_SDBN) is one of the highest titer reported for microbial production of 2,3-BDO. While microbial production of 2,3-BDO has been studied in various species of microorganism and various ways [37], attempts in an industrial polyploid S. cerevisiae are novel [38]. Besides, the results of cassava hydrolysate fermentation using the engineered polyploid S. cerevisiae are not inferior even compared with those of bacteria including K. oxytoca [39].…”
Section: Discussionmentioning
confidence: 99%
“…In recent study, S. cerevisiae was shown to produce 81.0 g/l 2,3-BD in a fed-batch fermentation strategy using glucose as a carbon source. For reaching such high concentration, pyruvate carbon flux tugging strategy was used to reduce dominant ethanol production, thus increased 2,3-BD production [51]. In another study, a high 2,3-BD production was achieved by modulating the xylose metabolic pathway in engineered S. cerevisiae .…”
Section: Optimization Of Different Parameters For the Enhanced 23- Bmentioning
confidence: 99%